INCREASING MATHEMATICS LEARNING INTERACTIONS USING COOPERATIVE LEARNING THINK PAIR SHARE ON STUDENTS OF CLASS VIII B IN SMP MUHAMMADIYAH 2 GAMPING YOGYAKARTA - Dwi Endarto; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This study was conducted because of the low interaction mathematics learning. The purpose of this study seeks to increasing interaction of mathematics learning in class VIII B of SMP Muhammadiyah 2 Gamping on second semester in academic year 2015/2016 using Model Cooperative Learning Think Pair Share. This research was classroom action research. The subjects were students of class VIII B of SMP Muhammadiyah 2 Gamping many as 30 students. The object of research is the application of Model Cooperative Learning Think Pair Share. Data collection techniques such as observation, interviews, and tests. Analysis of data using data analysis observation, analysis of interview data and test. This research is consisting of three cycles that include planning, action, observation and reflection. Research result showed that increased interaction study mathematics. Based on the observation of the data are the average percentage increase interaction mathematics learning in each cycle an average of 55% to the category of "enough" in Cycle I to 58.05% with the category of "enough" in Cycle II became 79.17% with category of "strong" in Cycle III. The increase also occurred at an average of 65.34 cycles of the test results on the first cycle increased to 76.5 in Cycle II subsequently rose to 81.67 in Cycle III. And on mastery learning from 60% in the first cycle increased to 73.34% in Cycle II then increased again to 80% in Cycle III. Thus the results of the comparison between the results achieved with the targets set, has also shown that optimal results.